Design and Implementation of BLDC Motor with Integrated Drive Circuit - Joon Sung Park; Ki-Doek Lee (Institute of Advanced Engineering and Science, 2017)
The trend in the motor applications is to reduce weight and volume by increasing the efficiency. Because of the advantage of high efficiency and high density, interest in brushless DC motors and drives is increasing. Unlike DC motors, the brushless DC (BLDC) motors require inverter circuit and position detector. In this paper, we deal with the optimization of the BLDC motor, the inverter, and the position detector. The inverter is optimized to be mounted on the BLDC motor. This paper deals primarily with the design and implementation aspects of the BLDC motor and the integrated drive circuit. Experimental results for the prototype of the BLDC motor with integrated dirve circuit in the laboratory are presented to validate the feasibility.